Lymphocytopenia and occupational exposures among pattern and model makers. - Demers, Paul A.; Schade, W. J.; Demers, R. Y. (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--The study was performed to examine the relationship between a high prevalence of lymphocytopenia observed during a cancer screening program for pattern and model makers, who produce industrial prototypes and patterns, and 15 occupational exposures. METHODS--The cases (N = 83) were workers with lymphocyte counts of less than 1000, while the referents (N = 529) had counts of 1500 or higher. Exposures at the current workplace, and at up to 19 previous pattern and model shops, were assessed with the use of a questionnaire. RESULTS--Elevated risks were associated with exposure to epoxy resins [odds ratio (OR) 1.94, 95% confidence interval (95% CI) 1.02-3.70) and plastic dusts (OR 2.60, 95% CI 1.19-5.68) after adjustment for age and smoking status. No clear associations were found with duration of exposure or percentage of time potentially exposed. Although the results were based upon small numbers, epoxy resins and wood dust displayed the most consistent relationships in an analysis of changes in lymphocyte count and exposure status over time. CONCLUSION--While firm conclusions cannot be drawn, the strongest associations observed in this study were for exposure to epoxy resins.